MiR-29b regulates expression of collagens I and III in chondrogenically differentiating BMSC in an osteoarthritic environment. Issue 1 (December 2017) - Mayer, Ute; Benditz, Achim; Grässel, Susanne
Abstract Osteoarthritis (OA) is characterized by a slowly progressing, irreversible loss of articular cartilage. Tissue engineering approaches for cartilage regeneration include stem cell-based strategies but not much is known about their repair capacity in an OA microenvironment. The aim of the present study was to identify factors regulating collagen expression during chondrogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSC) in an OA microenvironment. Coculture with OA cartilage induced miR-29b expression in BMSC which inhibited collagen I and III expression. Elevated miR-29b expression resulted in higher caspase 3/7 activity and promoted apoptosis of BMSC in part by directly inhibiting the anti-apoptotic proteins Bcl-2 and Mcl-1. Stimulation with IFN-γ induced miR-29b expression in BMSC. Our results suggest that miR-29b affects BMSC-based OA cartilage regeneration because expression of collagen III, mainly produced by undifferentiated BMSC, and collagen I, a marker for dedifferentiated chondrocytes, are inhibited by miR-29b thus influencing composition of the newly formed ECM. This might be critical to avoid formation of inferior fibrocartilage instead of hyaline cartilage. Furthermore, higher miR-29b expression promotes apoptosis either preventing excessive cell growth or reducing the number of BMSC undergoing chondrogenesis. Thus, miR-29b has both supportive but possibly also unfavourable effects on BMSC-based OA cartilage regeneration.